2013
DOI: 10.1167/iovs.13-12250
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Correlation Between the Spatial Distribution of A2E and Lipofuscin Fluorescence in the Human Retinal Pigment Epithelium

Abstract: This report to our knowledge is the first description of the spatial distribution of A2E in the human RPE by imaging mass spectrometry. These data demonstrate that the accumulation of A2E is not responsible for the increase in lipofuscin fluorescence observed in the central RPE with aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 141 publications
(138 citation statements)
references
References 28 publications
8
129
0
1
Order By: Relevance
“…At the present point in RPE research, the mixture of compounds responsible for macular RPE AF is uncertain. As noted, prior literature suggests that a major macular fluorophore is A2E, but we now know that A2E is present here in small quantities only [18,26]. Hence, consideration must also be given to other candidates, including the known species just listed and others yet to be discovered.…”
Section: Application: Fluorophore Signal Recovery In the Human Rpementioning
confidence: 86%
See 1 more Smart Citation
“…At the present point in RPE research, the mixture of compounds responsible for macular RPE AF is uncertain. As noted, prior literature suggests that a major macular fluorophore is A2E, but we now know that A2E is present here in small quantities only [18,26]. Hence, consideration must also be given to other candidates, including the known species just listed and others yet to be discovered.…”
Section: Application: Fluorophore Signal Recovery In the Human Rpementioning
confidence: 86%
“…The fluorescent bisretinoid A2E was long considered to be dominant in the RPE, because it was abundant and well characterized, and it was considered the major component across the entire RPE layer [17]. In 2013, imaging mass spectroscopy (IMS) revealed that A2E has strong regional variations in its tissue distribution, casting doubt on its role as a major disease initiator [18] and suggesting that additional compounds must be considered. There is extensive literature on bisretinoid biochemistry and the search for candidate RPE fluorophores [19,20].…”
Section: Application: Fluorophore Signal Recovery In the Human Rpementioning
confidence: 99%
“…It was originally thought A2E correlated with AMD (Suter et al 2000), but later work found A2E primarily accumulated in the periphery of AMD eyes (Bhosale et al 2009), not in the macula. Furthermore, later work also demonstrated that lipofuscin only poorly predicted lesion spread in GA (Hwang et al 2006) and that the presence of A2E and lipofuscin did not even correlate with one another (Ablonczy et al 2013). Together, these data indicate A2E might be largely irrelevant to AMD and that visual cycle therapeutics like fenretinide would have little chance of having a protective effect in patients.…”
Section: Perspectives On Future Directionsmentioning
confidence: 99%
“…only in the darkest zones of the retina [57]. When the same technology was applied to the eyes of ABCA4…”
Section: Phototoxicitymentioning
confidence: 99%
“…In addition, ABCA4 −/− mice who received vitamin E, a potent inhibitor of LB oxidation [44], displayed 54% more LBs than controls. Studies in humans, using luorescence microscopy for quantifying lipofuscin, and MALDI-IMS (high-resolution matrix assisted laser desorption-ionization imaging mass spectrometry) for detecting A2E showed that lipofuscin luorescence colocalized with A2Eonly in the darkest zones of the retina [57]. When the same technology was applied to the eyes of ABCA4…”
mentioning
confidence: 99%